Prospects for global current account rebalancing - Kimberly Beaton; Carlos De Resende; René Lalonde; Stephen Snudden (Bank of Canada, 2010)
The authors use the Bank of Canada's version of the Global Economy Model, a multi-country, multi-sector dynamic stochastic general-equilibrium model with an active banking system (the BoC-GEM-FIN), to study the evolution of global current account balances following the recent global financial crisis. More specifically, they use several shocks from the model to generate a simulated baseline scenario that mimics: (i) the initial, pre-crisis state of disequilibrium in global current account balances, and (ii) the effects of the crisis, including those of the policy responses undertaken worldwide. The authors find that a sufficient set of conditions and policies for a sustainable resolution of the global current account imbalances relies on three key elements: (i) a continuous upward adjustment of U.S. private savings, (ii) fiscal consolidation in advanced countries, and (iii) an orderly adjustment of exchange rates. These three criteria facilitate a gradual decline in the U.S. current account deficit going forward. A fourth key element, the implementation of policies aimed at stimulating domestic demand in emerging Asia, is needed to ensure that the counterpart of the decrease in the U.S. current account deficit is mainly a reduction in the surpluses of emerging Asia. Sensitivity analysis based on deviations from these conditions illustrates the factors behind the main results and the costs associated with the alternative scenarios considered.
Keywords: E21; F01; F32; 330; balance of payments and components; business fluctuations and cycles; international topics; recent economic and financial developments; Globalisierung; Internationaler Finanzmarkt; Finanzmarktkrise; Zahlungsbilanzungleichgewicht; Theorie; Welt